1992
DOI: 10.1111/j.1532-5415.1992.tb01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Low to Moderate Intensity Endurance Training in Healthy Older Adults: Physiological Responses after Four Months

Abstract: This study demonstrated that a large scale training program is feasible for healthy older people, that physiologic improvements can be measured after 16 weeks of low-to-moderate-intensity training, and that mechanisms of adaptation to exercise may be different in elderly subjects from those in younger ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
3
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 30 publications
5
47
3
1
Order By: Relevance
“…However, after 4 weeks of detraining, only some of the gain in VO 2max remained. The significant increase in VO 2max in our study was not unexpected, because similar increases have been reported by most aerobic-training studies of 16-20 weeks duration in men of similar ages (Hepple, Mackinnon, Goodman, Thomas, & Plyley, 1997;Pickering et al, 1997;Posner et al, 1992). However, the significant increase in leg strength of the aerobically trained men in our study is in contrast to other cross-sectional and longitudinal studies of aerobically trained older men (Dreyer et al, 2006;Hagberg et al, 1989;Sipila, Viitasalo, Era, & Suominen, 1991; Note.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, after 4 weeks of detraining, only some of the gain in VO 2max remained. The significant increase in VO 2max in our study was not unexpected, because similar increases have been reported by most aerobic-training studies of 16-20 weeks duration in men of similar ages (Hepple, Mackinnon, Goodman, Thomas, & Plyley, 1997;Pickering et al, 1997;Posner et al, 1992). However, the significant increase in leg strength of the aerobically trained men in our study is in contrast to other cross-sectional and longitudinal studies of aerobically trained older men (Dreyer et al, 2006;Hagberg et al, 1989;Sipila, Viitasalo, Era, & Suominen, 1991; Note.…”
Section: Discussioncontrasting
confidence: 56%
“…Leg extension is an adequate measure of strength per se, but not necessarily an adequate measure of functional strength (Sale, 1988). The 21% increase in leg strength found in the current study is substantially less than the increase in strength found after similar periods of high-and low-intensity resistance training in older individuals (Hortobagyi et al, 2001;Posner et al). The greater increase in strength found with resistance-training protocols most likely reflects the higher intensities used with resistance training and the specific nature of the resistancetraining exercise (Macaluso & De Vito, 2004).…”
Section: Vo 2maxcontrasting
confidence: 51%
“…또한 운동은 신체 활동의 한 범주로 체력을 유지하고 향상시키기 위하여 계획적 으로 반복 수행되는 구조화된 활동을 의미하는데 조깅, 수영 등 규칙적인 운동 (Posner et al, 1992;Yun et al, 2002)이나 여 가활동 (Sanderson et al, 2002;Pullen et al, 2001)으로 신 체활동을 평가한 연구들이 대부분이어서 가사 활동 등 일상생 활에서의 신체활동이 주가 되는 재가 노인의 신체활동을 정확히 평가하지 못한 제한점이 있었다 (Kaplan et al, 2001;Plonczynski et al, 2008). Control and Prevention, 2008;Wilcox et al, 2003)과 신체활동에 영향을 미칠 수 있는 신체 적, 정신적 건강 (Carruth & Logan, 2002;Semanik, Wilbur, Sinacore, & Chang, 2004), 사회적지지 (Wilcox et al, 2003), 이용할 수 있는 건강서비스 (Pullen et al, 2001) 등이 다를 수 있기 때문에, 노년기의 신체활동 참여율을 높이기 위해서 거주 지별로 노인의 특성을 고려한 신체활동 증진 전략을 개발해야 한다는 주장 (Plonczynski et al, 2008;Scharff, Homan, Kreuter, & Brennan, 1999 (Table 1).…”
Section: 그러나 대부분의 연구에서 일부 변수에 초점을 두어 수행되었 기 때문에 여러 가지 변수를 포괄하여 노년기 신체unclassified
“…Likewise, endurance training has been examined in elderly people who performed 20 to 40 minutes of exercise for 12 to 16 weeks ranging from low to high intensity (40% to 70% of heart rate reserve). 12,20 The types of training performed by elderly people who are healthy and those who are frail include walking, cycling, and water and land aerobics. Training has been shown to improve maximal oxygen consumption and 6-minutewalk distance as well as measures of health status.…”
mentioning
confidence: 99%